Eosinophil Activation Status in Separate Compartments and Association with Asthma - Johansson, Mats W. (Frontiers in Medicine, 2017)
Asthma is frequently characterized by eosinophil-rich airway inflammation. Airway eosinophilia is associated with asthma exacerbations and likely plays a part in airway remodeling. Eosinophil recruitment from the blood stream depends on circulating eosinophils becoming activated, which leads to eosinophil arrest on activated endothelium, extravasation, and continued movement through the bronchial tissue by interaction with the extracellular matrix (ECM). Circulating eosinophils can exist at different activation levels, which include non-activated, or pre-activated (sensitized or “primed”). Further, the bloodstream may lack pre-activated cells, due to such eosinophils having arrested on endothelium or extravasated into tissue. Increased expression, and in some instances decreased expression of cell-surface proteins, including CD44, CD45, CD45R0, CD48, CD137, neuropeptide S receptor, cytokine receptors, Fc receptors, and integrins (receptors mediating cell adhesion and migration by interacting with ligands on other cells or in the ECM), and activated states of integrins or Fc receptors on blood eosinophils have been reported to correlate with aspects of asthma. A subset of these proteins has been reported to respond to intervention, e.g., with anti-interleukin (IL)-5. How these surface proteins and the activation state of the eosinophil respond to other interventions, e.g., with anti-IL-4 receptor alpha or anti-IL-13, is unknown. Eosinophil surface proteins suggested to be biomarkers of activation, particularly integrins, and reports on correlations between eosinophil activation and aspects of asthma are described in this review. Intermediate activation of beta1 and beta2 integrins on circulating eosinophils correlates with decreased pulmonary function, airway inflammation, or airway lumen eosinophils in non-severe asthma. The correlation does not appear in severe asthma, likely due to a higher degree of extravasation of pre-activated eosinophils in more severe disease. Bronchoalveolar lavage (BAL) eosinophils have highly activated integrins and other changes in surface proteins compared to blood eosinophils. The activation state of eosinophils in lung tissue, although likely very important in asthma, is largely unknown. However, some recent articles, mainly on mice but partly on human cells, indicate that tissue eosinophils may have a surface phenotype(s) different from that of sputum or BAL eosinophils.